Effect of User Proximity on Internal Quad Band Mobile Phone MIMO/Diversity Antenna Performances - Singh H.S.; Meshram M.K. (My University, 2025)
This paper is in continuation of our previous published work, in which effect of user’s body is studied for quad band diversity antenna. The antenna has been successfully designed and studied in the free space. In this study, three kinds of user effects on previously proposed antenna are considered, namely, “Specific Anthropomorphic Mannequin (SAM) head and PDA hand (Talk mode)”, “Personal Digital Assistants (PDA) hand (Data mode)”, and “Dual hands (Read mode)”. There are two different positions of the quad band antenna over mobile circuit board is considered i.e., antenna at top position and bottom position of mobile circuit board. In the user proximity, the optimal location of antenna over circuit board is chosen for real application based on the antenna performance parameters i.e. S-parameters, diversity performances, and radiation performances. The specific absorption rate (SAR) for American standard (1.6 W/kg average over 1 g tissues) and European standard (2 W/kg average over 10 g tissues) is calculated for the top and bottom position of the MIMO antenna elements and it is found that the values of SAR is well below the standard limit of FCC as well as European standard. Based on the study, it is found that antenna at top position of mobile circuit board shows overall better performance in the presence of user’s body. © 2016, Springer Science+Business Media New York.